Soft Computing: Theories and Applications Proceedings of SoCTA 2017 - Ray, Kanad; Sharma, Tarun K.; Rawat, Sanyog; Saini, R. K.; Bandyopadhyay, Anirban; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book focuses on soft computing and its applications to solve real-world problems occurring in different domains ranging from medicine and healthcare, and supply chain management to image processing and cryptanalysis. It includes high-quality papers presented in the International Conference on Soft Computing: Theories and Applications (SoCTA 2017), organized by Bundelkhand University, Jhansi, India. Offering significant insights into soft computing for teachers and researchers alike, the book inspires more researchers to work in the field of soft computing.
Chapter 1: An Analysis of Authors productivity in RFID & Supply Chain Management -- Chapter 2: Meta Heuristic Techniques Study for Fault Tolerant in Cloud Computing Environment: A Survey Work -- Chapter 3: Complexity Metrics for Component Based Software System -- Chapter 4: DESIGN AND ANALYSIS OF ON-CHIP LOW POWER, LOW DROP-OUT VOLTAGE REGULATOR using FFRC and MCC Techniques -- Chapter 5: Study and Analysis of Back-Propagation Approach in Artificial Neural Network using HOG Descriptor for Real-time Object Classification -- Chapter 6: Identification of relevant stochastic input variables for prediction of daily PM10 using Artificial Neural Networks -- Chapter 7: Field based Weighting Information Retrieval on Document field of Ad hoc dataset .
Keywords: Computational intelligence; Signal processing; Telecommunication; Computational Intelligence; Signal, Speech and Image Processing; Communications Engineering, Networks